A cross-case analyses of laboratory professionals-patients interaction for patients accessing laboratory services at University of Cape Coast hospital and Ewim Polyclinic in the Cape Coast Metropolis, Ghana - Patrick Adu (BMC, 2021)
Abstract Background There is scarcity of data on experiences of patients who access laboratory services during hospital visits in sub-Saharan Africa. This study sought to evaluate the depth of laboratory professionals-patient interactions during pre- and post-sampling period at two hospitals in Ghana. Methods This study used real time observations of patient-laboratory staff interactions to collect first-hand data. Additionally, two separate sets of semi-structured questionnaires were used to collect data on the experiences of patients and laboratory professionals. Data were entered into Microsoft Excel and analysed using SPSS version 25. Results Inadequate laboratory space is a major factor limiting adequacy of patients-laboratory professionals' interactions. Overall, even though the laboratory professionals (93.3%) overwhelmingly agreed to the need to inform patients about the turnaround time of the respective laboratory testing, this was not routinely done. Irrespective of patients' educational attainment, patients were poorly informed about their respective laboratory tests. Although both patients and laboratory professionals (60.0% vs 63.6% respectively) indicated that the test requester has responsibility to inform patients about their laboratory testing, only 29.1% of patients indicated having received such explanations. Furthermore, although 28.1% of patients indicated knowing the specifics of their respective test requisition, only 15% could correctly identify their requested laboratory testing. Conclusion There is the need for standard operating protocols to standardize practitioner-patient interaction at the two facilities. Moreover, there is the need for laboratory staff-test requester engagement to clearly delineate who has what responsibilities regarding informing patients about laboratory testing.